Caracterização de genes de reparo de DNA em cana-de-açúcar - Medeiros, Amanda Larissa Marques de (2015)
Sugarcane is an important culture for Brazil that holds almost half of all worldwide productivity. Plants face many challenges, because of biotic and abiotic stresses presents in the production field, which could prevent plants from reaching their genetic potential. As consequence, those stresses can generate Reactive Oxygen Species – ROS – that can cause damages on DNA. Another consequence of stress is the early-flowering process, which contributes for a reduction on yield. In this context, the aim of this work is to characterize ScMUTM1 and ScMUTM2, two DNA glycosylases belonging to base excision repair pathway; and identify genes potentially related to stress and DNA repair in two sugarcane cultivars with contrasting flowering phenotypes. The characterization of the DNA glycosylases included the construction of vector to over express the recombinant proteins ScMUTM1 and ScMUTM2; they will be used in a near future to purification of these proteins and use in enzymatic assays. It was also made a phylogenetic reconstruction of this gene in plants and analysis of its promoter. With the phylogenetic analysis, it is possible to observe the presence of these genes grouped inside a branch with monocots and another one with dicots. This suggests that the duplication of this gene probably occurred after the separation of these two groups. The analysis of the promotor of MUTM shows of the presence of stress-related regulatory motifs at ScMUTM2 promoter, when compared with ScMUTM1. This may suggests that ScMUTM1 might be suffering sub functionalization process. After the analysis of microarrays data, it is observed an up-regulation from some stress-related genes in one of the conditions analyzed, related to early flowering process.